Cyberbullying among youth in Malaysia - Lai, Chee Sern; Mohamad, Mimi Mohaffyza; Lee, Ming Foong; Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Rosli, D’oria Islamiah; Chang, Wilson Vui Seng (Indeks Belia Malaysia, 2016)
The purpose of this research was to survey the current situation concerning cyberbullying among youth in Malaysia. Specifically, this research aimed at finding out the prevalence of cyberbullying among youth based on demographic data and the common types of cyberbullying tactic. The survey method was adopted as the research design in which a set of questionnaire was developed to collect the data. A total of 1406 respondents were selected in this research. In general, the research findings reveal that majority of the respondents had been cyberbullied before. The Malays community yielded the highest percentage of cyberbullied victims. In addition, the result also shows that female cyber users were usually targeted as the cyberbully victim. The most common type of cyberbully tactic was through receiving offensive/ pornographic materials. Effective and pragmatic steps have to be taken in order to mitigate the cyberbullying problem among Malaysian youth.